2015
DOI: 10.1371/journal.pone.0122681
|View full text |Cite
|
Sign up to set email alerts
|

More than Half of High School Students Report Disordered Eating: A Cross Sectional Study among Norwegian Boys and Girls

Abstract: Disordered eating and eating disorders are of great concern due to their associations with physical and mental health risks. Even if adolescence has been identified as the most vulnerable time for developing disordered eating, few studies have used a broad spectrum of criteria to investigate the prevalence of disordered eating among high school students of both genders, in different programs of study, nor assessed correlates of disordered eating among this important target group. The purposes of this study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 70 publications
1
23
0
1
Order By: Relevance
“…DEABs in both genders might also be explored using more complex information (including BMI, drive for muscularity and drive for thinness, history of disordered eating, etc.) as reported in the other studies [4]. It would be reasonable to assess the body image and DEABs in the classification groups of weight-sensitive sports, i.e., in gravitational, weight class, and aesthetically judged sports [21] in larger samples in future studies.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…DEABs in both genders might also be explored using more complex information (including BMI, drive for muscularity and drive for thinness, history of disordered eating, etc.) as reported in the other studies [4]. It would be reasonable to assess the body image and DEABs in the classification groups of weight-sensitive sports, i.e., in gravitational, weight class, and aesthetically judged sports [21] in larger samples in future studies.…”
Section: Discussionmentioning
confidence: 68%
“…Unfortunately, the results of the studies on the prevalence of DEABs in sport involved adolescents and controls are inconsistent. Some studies showed a higher prevalence of disordered eating among the controls compared to the athletes [4,24,32,33]. Other studies concluded that athletes competing in weight-sensitive sports reported greater rates of eating pathologies [34][35][36], however, other studies in elite adolescent athletes did not confirm these findings [32,37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In doing so, such methods typically result in much higher prevalence estimates(Torstveit, Aagedal-Mortensen, & Stea, 2015;Vega Alonso, Rasillo Rodriguez, Lozano Alonso, Rodriguez Carretero, & Martin, 2005). In doing so, such methods typically result in much higher prevalence estimates(Torstveit, Aagedal-Mortensen, & Stea, 2015;Vega Alonso, Rasillo Rodriguez, Lozano Alonso, Rodriguez Carretero, & Martin, 2005).…”
mentioning
confidence: 99%